Problems and directions of improving the insurance of agricultural crops and plantings of perennial plantations against the risks of natural emergencies - N. N. Semenova; A. Y. Averin (Аграрная наука Евро-Северо-Востока, 2021)
The simultaneous existence of two interrelated forms of state aid - subsidizing classical agricultural insurance and compensation for damage to affected regions from the federal budget - requires understanding the basic principles of interaction and assessing the mutual impact of these areas of support. The purpose of the study is to identify the problems of the development of crop insurance and planting of perennial crops against the risks of natural emergencies. The research was carried out in the context of insurance statistics of Russian regions using generally accepted methods. The conducted research revealed the negative dynamics of a significant decrease in the volume of crop insurance of agricultural crops in 2016-2020. Regional authorities in the conditions of a single subsidy are not interested in the independent distribution of funds allocated by the state for the development of agricultural insurance. This is due to the fact that when the agricultural sector has significant losses as a result of the impact of natural disasters, the practice of introducing an emergency regime by the region is widespread. Which gives grounds for receiving compensation for half of the amount of damage directly from the federal budget. This determines the main problem of the development of classical agricultural insurance - the lack of expediency and material interest in this mechanism of protection of property interests both on the part of producers of agricultural products and on the part of regional authorities. In this regard, a brief justification was given for the feasibility of transforming the mechanism for providing direct assistance to the regions from the federal budget into a separate area of crop risk insurance in case of a natural emergency. This line of support will complete the classic multi-risk agricultural insurance.